Identifying and selecting gender-responsive climate-smart socio-technical innovation bundles: Framework for a situational analysis - Gartaula, Hom Nath; Nchanji, Eileen; Puskur, Ranjitha; Mukhopadhyay, Prama; Ketema, Dessalegn Molla; Lutomia, Cosmas Kweyu; Chadha, Deepali; Mapedza, Everisto D. (CGIAR Initiative on Gender Equality, 2023)
This framework for a situational analysis aims to guide the process of identifying entry points for designing and implementing context-relevant and gender-responsive STIBs together with farmers and relevant stakeholders, that have explicit outcomes for women’s empowerment and climate resilience. It is part of the toolbox of the CGIAR Initiative on Gender Equality (HER+).